Ewe performance in the post-weaning phase and structural characteristics of Brachiaria brizantha cultivars in the dry season - Silva, Alex Álvares da; Difante, Gelson dos Santos; Emerenciano Neto, João Virgínio; Gurgel, Antonio Leandro Chaves; Fernandes, Leonardo Santana; Campos, Nathalia Rafaela Fidelis; Carvalho Netto, Roldão Teixeira de; Santos Santana, Juliana Caroline (Acta Scientiarum. Animal Sciences, 2021)
The objective of this study was to examine the performance of ewes in the post-weaning phase and the structural characteristics of Brachiaria brizantha cultivars in the dry season. The treatments were represented by four Brachiaria brizantha cultivars (Piatã, Marandu, Paiaguás, and Xaraés), which were evaluated in a randomized-block design with two replicates for the forage variables and eight replicates for the animal performance variables. Canopy height, masses of forage and morphological components and chemical composition of morphological components were evaluated. Thirty-two ½ Santa Inês and ½ Dorper sheep with an initial body weight (BW) of 22.7 ± 1.2 kg were used. Average daily gain (ADG – kg animal-1 day-1), stocking rate (in animal units [AU] = 30 kg of body weight) and weight gain per area (kg ha-1 day-1) were measured. There was no cultivar effect (p > 0.05) on the structural characteristics of the pasture. The highest crude protein content in the leaf blade (11.8%) were found in cultivar Marandu. Average daily gain was higher in the animals that grazed on cultivar Marandu (0.08 kg animal-1 day-1) as compared with cultivars Xaraés (0.05 kg animal-1 day-1) and Piatã (0.04 kg animal-1 day-1), whereas the ewes that grazed on cultivar Paiaguás showed intermediate ADG values (0.06 kg animal-1 day-1). There was no difference between the cultivars for stocking rate (9.2 AU). Weight gain per area was highest in cultivar Marandu (0.33 kg ha-1 day-1) and lowest in cv. Piatã (0.16 kg ha-1 day-1). Brachiaria brizantha cultivars Piatã, Marandu, Paiaguás and Xaraés proved to be forage options for the post-weaning phase of ewes supplemented with concentrate in the dry season.